Pengembangan Media Pembelajaran Musikalisasi Puisi untuk Meningkatkan Kemampuan Belajar Siswa Kelas IX - Agnes Linda Astuti Gea; Ester Claryta Telaumbanua; Antonius Zendrato; Arozatulo Bawamenewi (Departement of Mathematics Education, 2023)
This study was done to improve the skills of junior high school pupils employing poetry musicalization in educational media. This study's goals were to boost students' motivation and interest in poetry music, decrease learning process dullness, and especially assess the efficacy of poetry music medium.The Research and Development (R&D) technique was employed in this study as a roadmap for carrying out development. Researchers employed questionnaires for material expert validation and student response to gather data for their studies. The percentage of student test results falling under the category of